(untitled) (Research, Society and Development, 2024)
Pregnancy-Specific Hypertensive Disease (GHD) causes changes in the mother’s body that are different from those observed in a normal pregnancy, affecting several organic systems. In this sense, nutrition during pregnancy is fundamental for maternal and fetal health, directly contributing to the baby’s development and the mother’s well-being. The study aimed to carry out a systematic review of health strategies to prevent gestational hypertension. For this purpose, the systematic review method was used. The results and analysis of the publications reveal effective practices and interventions in the context of gestational hypertension, highlighting the importance of nutritional guidance in prenatal care and the need for effective nursing practices to reduce the incidence of gestational hypertension. The present study concludes by drawing the attention of competent authorities to the formulation of public policies and health practices that meet the needs of pregnant women and contribute to improving prenatal care and promoting effective strategies for the prevention of gestational hypertension.